A morphometric and analytical cadaver dissection study of a tumor-simulation balloon model. (March 2018) - Bozkurt, Baran; Belykh, Evgenii; Yağmurlu, Kaan; Agrawal, Abhishek; Chang, Steve W.; Staren, Michael S.; Spetzler, Robert F.; Zabramski, Joseph M.; Preul, Mark C.
Highlights: Central skull base lesion surgery risks damage to vital structures and nerves. Anatomical knowledge is crucial for sellar and parasellar region lesion surgery. Mass effects of intracranial tumors on central skull base anatomy are evaluated. The model significantly displaces central anatomical sella-associated structures. Simulating mass effect on normal anatomy may enhance neurosurgical training. Abstract: We quantified the effects on anatomical cadaver dissection of a balloon-inflation tumor model positioned in the parasellar region and approached through an orbitozygomatic (OZ) craniotomy. A modified supraorbital OZ was performed bilaterally on 5 silicon-injected cadaver heads. Ten predetermined anatomical points assigned using a frameless stereotactic device were used to measure the working area of exposure, degree of surgical freedom, and horizontal and vertical angles of attack to specific target points before and after inflation of a balloon catheter mimicking a parasellar tumor. Balloon inflation displaced the central anatomical structures (pituitary stalk, lamina terminalis, anterior chiasm, and internal carotid artery [ICA]–posterior communicating artery and ICA-A1 junctions) by 14–51% (p ≤ .05). With tumor simulation, the vertical angle of attack increased by 67% (p < .01), while the area of exposure increased by 83% (p < .01) and surgical freedom increased by 58% (p < .01). This tumor model also significantly displaced central anatomical sella-associated structures. Compared to a normal anatomical configuration, the tumor simulation (balloon) opened surgical corridors (especially vertical) and acted as a natural retractor, widening the angle of access to the infundibular apex–hypothalamic junction. Although this model cannot exactly mimic a tumor mass in a patient, the effects of tumor compression and sequential displacement of important structures can be combined into and then assessed in a cadaveric neurosurgical anatomical scenario for training and research.